A DFT-D4 investigation of the complexation phenomenon between pentachlorophenol and β-cyclodextrin - Zoubir Kabouche; Youghourta Belhocine; Tahar Benlecheb; Ibtissem Meriem Assaba; Abdelkarim Litim; Rabab Lalalou; Asma Mechhoud (Chimica Techno Acta)
Density functional theory (DFT) calculations based on the BLYP-D4 and PBEh-3c composite methods were performed for investigating the encapsulation mode of pentachlorophenol (PCP) inside the cavity of β-cyclodextrin (β-CD). Different quantum chemical parameters such as HOMO, LUMO, and HOMO–LUMO gap were calculated. Complexation energies were computed at the molecular level to provide insight into the inclusion of PCP inside the β-CD cavity. The Independent gradient model (IGM) approach was applied to characterize the non-covalent interactions that occurred during the complex (PCP@β-CD) formation. Two modes of inclusion were considered in this work (modes A and B). Calculated complexation energies as well as the changes in enthalpy, entropy, and free Gibbs energy exhibit negative values for both modes A and B, indicating a thermodynamically favorable process. Weak Van der Waals interactions and one strong intermolecular hydrogen bond act as the main driving forces behind the stabilization of the formed most stable complex. This study was carried out to explore the potential use of the β-CD as a host macrocycle for sensing and capturing pentachlorophenol.